The Effect of Starch-Lactose Filler Ratio on the Quality Characteristics of Meniran Extract Capsule - Kawiyanto, Joko; Elina, Alifah Asri; Sasongko, Jessica Herlin Labella (Universitas Ahmad Dahlan, 2025)
The empirical utilization of medicinal plants by Indonesians has long been known as